EFEKTIFITAS APLIKASI INSPEKTA DALAM PENINGKATAN BUDAYA K3 DI PLN ULP KISARAN - Duwi Irpan Sukoco; Achmad Puariesthaufani (J-Com (Journal of Computer), 2023)
Abstract: Enhancing Occupational Health and Safety (OHS) culture is of paramount importance in industrial settings, especially in energy sectors like PLN. Inspekta, an information technology-based application, has emerged as a potential solution to boost awareness and compliance with OHS practices at PLN ULP Kisaran. However, a comprehensive evaluation of this application's effectiveness is still necessary. This research aims to assess the effectiveness of the Inspekta Application in fostering an OHS culture at PLN ULP Kisaran. Utilizing a combined approach of literature review, questionnaire surveys, and statistical analysis, the study collected and analyzed relevant data.The research findings reveal that the implementation of the Inspekta Application has had a positive impact on elevating the OHS culture at PLN ULP Kisaran. Improved employee awareness regarding OHS aspects and more efficient incident reporting stand out as significant outcomes. Statistical analysis also indicates a positive correlation between the utilization of the Inspekta Application and the enhancement of the OHS culture. Based on the research insights, it can be concluded that the Inspekta Application is effective in enhancing the OHS culture at PLN ULP Kisaran. The integration of information technology through such applications holds the potential to mitigate workplace accident risks and foster a safer and healthier working environment. Keywords: inspekta; ohs culture; workplace safety  Abstrak: Peningkatan budaya Keselamatan dan Kesehatan Kerja (K3) memiliki peran yang sangat penting dalam lingkungan industri, terutama di sektor energi seperti PT. Perusahaan Listrik Negara (PLN). Inspekta, sebuah aplikasi berbasis teknologi informasi, telah muncul sebagai solusi potensial untuk meningkatkan kesadaran dan kepatuhan terhadap budaya K3 di PT. PLN (Persero). Penelitian ini bertujuan untuk mengevaluasi efektivitas Aplikasi Inspekta dalam meningkatkan budaya K3 di PLN ULP Kisaran. Dengan pendekatan kombinasi studi literatur, survei kuesioner, dan analisis statistik, penelitian ini mengumpulkan dan menganalisis data yang relevan. Hasil penelitian baik dari kajian literature, observasi dan wawancara partisipatif menunjukkan bahwa Aplikasi Inspekta mendapat tanggapan positif yang signifikan dengan rata-rata indikator tanggapan diatas 50%, sehingga berdampak dalam memperkuat pemahaman budaya K3 di lingkungan kerja PLN. Penerapan Aplikasi Inspekta juga terbukti membantu dalam mengidentifikasi potensi bahaya K3, mendorong pelaporan bahaya, serta memungkinkan tindakan cepat setelah pelaporan melalui integrasi teknologi informasi guna mengurangi risiko kecelakaan kerja dan menciptakan lingkungan kerja yang lebih aman dan sehat. Kata Kunci: inspekta; budaya k3; keselamatan kerja